Oriental Culture In Transition : Hyderabad State (1853-1948) - Vaikuntham, Y., (Brill | Manohar Publishers & Distributors, 2018)
The culture of Hyderabad was not only the extension of the Mughal culture with geographical distinctiveness, but also regionalized with special features known as Deccani culture, a distinct form of Oriental Culture. This volume analyses how and to what extent the regional influences in Hyderabad dominated while assimilating the features of the British Raj. 'Paramountcy' was a canny and self-serving concept invented by the British in the nineteenth century to assert their 'indirect rule' over the Princely States. The British Residents were the eyes and ears of the Raj. The present volume analyses in detail to what extent the Western cultural forms were, enforced or assimilated, in the way of manners, customs, etiquette, dress code and protocol. It also examines how liberal, secular English education was diligently promoted, not only for princes and nobles of Hyderabad but also local administrators. The volume concludes how this confrontation and assimilation of oriental and Western cultures led to the evolution of a new regionalized culture in Hyderabad state.